Germinação e atividade de enzimas antioxidativas na caracterização da tolerância de cultivares de soja ao estresse hídrico - Santos Junior, Hamilton Carvalho dos (Universidade Federal de Viçosa, 2018)
A privação de quantidade adequada de água durante a implantação ou desenvolvimento de lavouras é o fator mais importante limitando a sobrevivência e produção comercial de plantas. A fase de germinação e desenvolvimento inicial de plântulas é a mais vulnerável aos efeitos da seca. Nos últimos anos, a ocorrência de déficit hídrico durante a implantação em lavouras de soja (Glycine max (L.) Merrill) tem sido comum, gerando grandes prejuízos advindos de dossel deficitário de plantas e consequente necessidade de replantio. É possível que nos próximos anos se inicie uma classificação e apresentação comercial da tolerância de cultivares de soja ao déficit hídrico durante a germinação e crescimento inicial de plântulas. Vários indicadores podem ser utilizados na avaliação da tolerância de sementes ao déficit hídrico durante a germinação e desenvolvimento inicial de plântulas. O teste de germinação tem bom potencial para acessar essa tolerância por se tratar da avaliação de uma característica complexa e que avalia a capacidade da semente em dar origem à uma plântula normal. Além disso, o vigor de lotes de sementes é um fator que deve ser considerado na avaliação de cultivares de soja quanto a tolerância ao déficit hídrico, pois lotes com maior vigor apresentam maior tolerância à condições de estresse. Isto posto, o objetivo deste estudo foi: i) classificar diferentes cultivares de soja quanto a tolerância de sementes ao déficit hídrico durante a germinação e desenvolvimento inicial de plântulas; ii) avaliar o teste de germinação como uma possível metodologia para acessar essa tolerância; e iii) avaliar a atividade de enzimas do sistema de defesa antioxidativo de cultivares contrastantes quanto à tolerância ao déficit hídrico. Sementes de 27 cultivares de soja foram produzidas em casa de vegetação e submetidas à avaliação quanto à tolerância ao déficit hídrico durante a germinação. Para isso, duas metodologias foram utilizadas e comparadas: a) análise multivariada de oito variáveis indicadoras da tolerância de sementes ao déficit hídrico, obtidas a partir de testes de germinação e vigor conduzidos no potencial -0,4 MPa: primeira contagem e a contagem final de sementes germinadas e de plântulas normais do teste de germinação, comprimento e biomassa de parte aérea e raiz de plântulas; e b) redução percentual dos valores obtidos na contagem de plântulas normais do teste de germinação entre testes conduzidos no potencial 0 e -0,4 MPa. Foram avaliadas as atividades das enzimas superóxido dismutase, catalase, peroxidase e peroxidase do ascorbato. A análise multivariada dos indicadores da tolerância apresentou resultados similares para a classificação de cultivares quanto à redução percentual dos valores obtidos comparando-se as contagens de plântulas normais do teste de germinação e testes conduzidos nos potenciais 0 e -0,4 MPa. As cultivares M8210IPRO, TMG132RR, TG1066RR, CD206RR, M7211RR, BMXPOTENCIARR e CD224 foram consideradas como as mais tolerantes ao estresse hídrico. As cultivares TMG1288RR, TMG1180RR, CD234RR e Ra628 foram consideradas como de tolerância intermediária. As cultivares M8644IPRO, TMG2181IPRO, M8372IPRO, TMG7062IPRO, M7739IPRO, TMG4182, M7110IPRO, TMG4185, ANTA82, BRS283, BRS184, Msoy6101, FUNDACEP 57 RR, BRS259, CD251RR e CD233 RR foram consideradas como mais sensíveis. Houve redução na atividade enzimática das enzimas catalase, peroxidase e peroxidase do ascorbato, enquanto houve aumento da atividade da superóxido dismutase, nas sementes sob déficit hídrico. Em geral, não houve diferença na atividade enzimática comparando-se as cultivares. A redução percentual dos valores obtidos no teste de germinação, conduzido com solução osmótica no potencial 0 e -0,4 MPa, pode ser utilizada como metodologia simples para acessar a tolerância de sementes de soja ao déficit hídrico.

The water privation on the field, as commonly known as drought, during the crop implantation or seedling initial development is the most important factor limiting plant survival and crop commercial production. The germination and seedling initial development phase is the most vulnerable to drought during the plant cycle. Soybean (Glycine max) is a crop of major importance regarding food security and economy to Brazil. On the last few years, the occurrence of hydric deficit during the implantation of soybean fields has been common, thus, losses were observed from plant deficient canopies and consequent re-seeding. On the following years, there is a possibility that soybean cultivars will be classified by the tolerance to hydric deficit during germination and initial seedling development. The germination test present good potential to access the tolerance of soybean seeds to hydric deficit considering that the test evaluate the capacity of a seed to become a normal seedling. Seed vigor can be defined as the potential of seeds to perform on the field under adverse conditions. Thus, seed vigor is a factor that must be considered on the evaluation of soybean cultivars under hydric deficit during germination and initial seedling development. Reactive Oxygen species (ROs) are a common product of the plant metabolism. However, the exaggerated production of reactive species is a consequence of the explosion of plants to drought. Plants are equipped with an ROs metabolizing system, however, this system is limited. In the occurrence of drought, ROs can be accumulated and thus provoke oxidative stress, causing metabolism alterations and further cell death. The ROs metabolizing system is composed of enzymatic and non-enzymatic mechanisms. The study of the mechanisms associated with the perception, response and adaptation to hydric stress present a primordial importance to plant breeding, genetic engineering and the creation on elite cultivars. Hence, the objective of this study is to i) classify different soybean cultivars regarding the tolerance to hydric deficit during germination and initial seedling development utilizing different indicators while considering the influence of seed vigor on the tolerance to stress; ii) the evaluation of the germination test as a possible methodology to access the tolerance of seeds to hydric deficit during germination and initial seedling development and; iii) the evaluation of the enzymatic activity of the antioxidant system between cultivars with contrasting tolerance levels. Two methodologies were used and compared: a) multivariate analysis of eight indicator variables to the tolerance of seeds to hydric deficit, obtained from tests conducted on the potential -0,4 MPa and b) percentage reduction of the values obtained from the counting of normal seedlings of the germination test, between tests conducted on the potentials 0 and -0,4 MPa. The evaluation of the enzymatic activity was performed by quantifying the enzymes superoxide dismutase, catalase, peroxidase, and ascorbate peroxidase of seedlings imbibed on solutions presenting the potentials 0 and -0,4 MPa. The negative potential was obtained by using PEG 6000. The multivariate analysis of the tolerance indicators presented similar results to the percentage reduction of the values obtained from the counting of normal seedlings of the germination test. This outcome suggest that the percentage reduction of normal seedlings counted between germination tests conducted on 0 and -0,4 MPa potentials can be used as a simple methodology to access the tolerance of soybean seeds to hydric deficit. The cultivars M8210IPRO, TMG132RR, TG1066RR, CD206RR, M7211RR, BMXPOTENCIARR and CD224 were considered as more tolerant to hydric stress during germination and initial seedling development. The cultivars TMG1288RR, TMG1180RR, CD234RR e Ra628 were considered of intermediary tolerance. The cultivars M8644IPRO, TMG2181IPRO, M8372IPRO, TMG7062IPRO, M7739IPRO, TMG4182, M7110IPRO, TMG4185, ANTA82, BRS283, BRS184, Msoy6101, FUNDACEP 57 RR, BRS259, CD251RR and CD233 RR were considered as sensible. Reduction on the enzymatic activity of the antioxidant system of seeds germinating under hydric was observed to the enzymes catalase, ascorbate peroxidase and peroxidase. The activity of the enzyme superoxide dismutase was increased. There was no significant difference between the cultivars considered as tolerant and sensible to the enzymes superoxide dismutase, peroxidase and ascorbate peroxidase. More studies are necessary to clarify the mechanisms of tolerance of soybean seeds to the hydric deficit during germination and seedling initial development.
Germination and the activity of antioxidant enzymes on the characterization of the tolerance of soybean cultivars to hydric stress
Keywords: Soja; Germinação; Plantas - Efeito da seca; Produção e Beneficiamento de Sementes